Investigation of Allocar TTM Targeting CD70 As a Potential Therapy for an Array of Hematological Malignancies - Panowski, Siler; Srinivasan, Surabhi; Van Blarcom, Thomas; Sommer, Cesar; Cheng, Hsin-Yuan; Pertel, Thomas; Santaguida, Marianne A; Galetto, Roman; Dunlop, Alan; Benjamin, Reuben; Sasu, Barbra (Blood, 2019)
Adoptive transfer of T cells expressing chimeric antigen receptors (CARs) is an exciting new therapy showing great promise in hematologic malignancies. Recent approval of two CD19-targeting CAR Ts, Kymriah® and Yescarta®, has been followed with promising results from BCMA clinical trials, showing that activity can extend to other targets. While these treatments show excellent potential for patients with an otherwise poor prognosis, a number of patients are still subject to relapse. These data suggest the potential utility of expanding the number of targets available for hematological malignancies. Autologous chimeric antigen receptor (CAR) T therapies use a patient's own T cells to produce the therapy. This approach has inherent challenges, including requiring significant time for production, complex supply chain logistics, separate GMP manufacturing for each patient, and variability in performance of patient-derived cells. Given rapid disease progression, combined with limitations associated with the autologous approach, many patients may not be able to receive CAR T therapy. Allogeneic CAR T (AlloCAR T) cell therapy, or “off-the-shelf” therapy which utilizes cells from healthy donors, may provide greater convenience with readily available CAR T therapy on-demand, reliable product consistency, and accessibility at greater scale for more patients. To create an allogeneic product, mRNAs encoding Transcription Activator-Like Effector Nucleases (TALEN®) designed to specifically disrupt the TRAC and CD52 genes are introduced to CAR Ts. These modifications are intended to minimize the risk of graft-versus-host disease and to confer resistance to ALLO-647, an anti-CD52 antibody that can be used as part of the conditioning regimen to deplete host alloreactive immune cells potentially leading to increased persistence and efficacy of the infused allogeneic cells. CD70 is a TNF superfamily member expressed on subsets of activated lymphocytes and is being explored as a CAR T target for renal cell carcinoma but may also be suitable for targeting hematological malignancies. To evaluate the potential of CD70 as a heme target, expression of CD70 RNA was compared to that of three known targets, CD19, BCMA, and FLT3, across a range of hematological malignancies by interrogating The Cancer Genome Atlas (TCGA) database. CD19 was expressed in lymphomas and leukemias, BCMA was expressed primarily in MM, and FLT3 expression was largely limited to AML. CD70 expression was observed across all 4 cancer types, indicating the potential broad utility CD70 CAR T cells. To determine cell-surface expression of these four targets, flow cytometry and receptor quantification was performed on a panel of heme cell lines. Good correlation was seen between RNA and the cell-surface protein expression of CD70. CAR T cells against each of the 4 targets were generated and evaluated in vitro. All CAR T cells exhibited robust specific activity against cells expressing their corresponding antigens. To ensure clinical relevance of results with cell lines, studies are currently ongoing to evaluate CD70 expression on primary patient samples and activity of CD70 CAR T cells against these same samples. Based on our studies, CD70 has a broad expression profile across a range of hematological malignancies and potent and selective CD70 CAR T activity has been demonstrated. Given these results, an allogeneic CD70 CAR T is expected to be clinically useful against a range of hematological tumor types either as a single agent or in combination with other CAR Ts. Panowski:Allogene Therapeutics: Employment, Equity Ownership. Srinivasan:Allogene Therapeutics: Employment, Equity Ownership. Van Blarcom:Allogene Therapeutics, Inc.: Employment, Equity Ownership. Sommer:Allogene Therapeutics, Inc.: Employment, Equity Ownership. Cheng:Allogene Therapeutics, Inc.: Employment, Equity Ownership. Pertel:Allogene Therapeutics: Employment, Equity Ownership. Santaguida:Notable Labs: Employment. Galetto:Cellectis Inc: Employment. Sasu:Allogene Therapeutics, Inc.: Employment, Equity Ownership.